Cloning and characterization of the A-factor receptor gene from Streptomyces griseus. - Onaka, H (1995)
A-factor (2-isocapryloyl-3R-hydroxymethyl-gamma-butyrolactone) and its specific receptor protein control streptomycin production, streptomycin resistance, and aerial mycelium formation in Streptomyces griseus. The A-factor receptor protein (ArpA) was purified from a cell lysate of S. griseus IFO 13350. The NH2-terminal amino acid sequences of ArpA and lysyl endopeptidase-generated fragments were determined for the purpose of preparing oligonucleotide primers for cloning arpA by the PCR method. The arpA gene cloned in this way directed the synthesis of a protein having A-factor-specific binding activity when expressed in Escherichia coli under the control of the T7 promoter. The arpA gene was thus concluded to encode a 276-amino-acid protein with a calculated molecular mass of 29.1 kDa, as determined by nucleotide sequencing. The A-factor-binding activity was observed with a homodimer of ArpA. The NH2-terminal portion of ArpA contained an alpha-helix-turn-alpha-helix DNA-binding motif that showed great similarity to those of many DNA-binding proteins, which suggests that it exerts its regulatory function for the various phenotypes by directly binding to a certain key gene(s). Although a mutant strain deficient in both the ArpA protein and A-factor production overproduces streptomycin and forms aerial mycelium and spores earlier than the wild-type strain because of repressor-like behavior of ArpA, introduction of arpA into this mutant abolished simultaneously its streptomycin production and aerial mycelium formation. All of these data are consistent with the idea that ArpA acts as a repressor-type regulator for secondary metabolite formation and morphogenesis during the early growth phase and A-factor at a certain critical intracellular concentration releases the derepression, thus leading to the onset of secondary metabolism and aerial mycelium formation. The presence of ArpA-like proteins among Streptomyces spp., as revealed by PCR, together with the presence of A-factor-like compounds, suggests that a hormonal control similar to the A-factor system exists in many species of this genus.